Book Review: CFP Board Financial Planning Competency Handbook - Jorge Ruiz-Menjivar (Journal of Financial Therapy, 2015)
The CFP Board Financial Planning Competency Handbook (2013) is reviewed as a resource that extends beyond financial planning to other helping professionals who work with money related issues.
Keywords: financial therapy; financial advising